Cervical cancer screening among HIV-infected women in an urban, United States safety-net healthcare system. (24th August 2018) - Barnes, Arti; Betts, Andrea C.; Borton, Eric K.; Sanders, Joanne M.; Pruitt, Sandi L.; Werner, Claudia; Bran, Andres; Estelle, Carolee D.; Balasubramanian, Bijal A.; Inrig, Stephen J.; Halm, Ethan A.; Skinner, Celette Sugg; et al.
Abstract : Objective: Little is known about cervical cancer screening and results patterns among HIV-infected (HIV+) women in real-world healthcare settings. We characterized two periods of screening opportunity. Design: Retrospective cohort. Setting: US safety-net healthcare system in Dallas County, Texas. Participants: We analyzed data from electronic medical records (EMR) of 1490 HIV+ women receiving care 2010–2014. Main outcome measures: At baseline, we categorized a woman's Pap status 15 months prior to index date as under-screened (vs. screened), and cytology result (normal vs. abnormal). Then, we examined screening completion and results, and colposcopy uptake and results after an abnormal screen, in the subsequent 15-month period. Results: More than half of women (56%) had no evidence of a Pap test (i.e. under-screened) at baseline. Under-screened women were more likely to be older (50–64 years), have diabetes, and unknown viral load; they were less likely to be Black, Hispanic, have Medicaid, recently pregnant, have a HIV clinic visit, or a CD4 + cell count at least 200 cells/μl. Nearly half of under-screened women (46%, n  = 383) remained under-screened in the subsequent 15 months. Among women under-screened at baseline who later completed screening and follow-up during the study period, 21 high-grade dysplasia and three cancers were diagnosed. Overall, 40% of women did not receive colposcopy when needed, with most failures to follow-up occurring in women who were under-screened at baseline. Conclusion: Most HIV+ women receiving care in a safety-net system did not receive sufficient screening for cervical cancer and remained at exceptionally high risk of developing high-grade dysplasia. Abstract : Supplemental Digital Content is available in the text